The New Normal: Enfreakment in Saga. Issue 1 (14th February 2019) - Lipenga, Ken Junior
This article draws on the award-winning fantasy comic Saga (Vaughan and Staples 2012–present ), in order to explore how it portrays bodily difference as the norm, presenting to us a fantasy reality that nevertheless uncannily parallels ours in many ways. If 'enfreakment' is the creation of the freak, the article argues that the comic achieves something that might be termed 'dis-enfreakment'. This article is mainly grounded in literary disability studies, drawing upon the work by Rosemarie Garland-Thomson and others. The article explores how Saga portrays racism, miscegenation, and homosexuality. The basic argument is that, through the presentation of a variety of races and species of life, Saga deliberately questions the very idea of 'normal' by presenting many co-existing forms of normalcy.